تحليل وقياس أثر تغيرات درجة الحرارة على انتشار فيروس كورونا في الجزائر باستخدام منهجية التكامل المشترك - حوشين, يوسف (جامعة الوادي university of eloued, 2023)
تهدف من الورقة البحثية إلى تحليل وقياس مدى تأثير درجة الحرارة على انتشار فيروس كورونا في الجزائر. من خلال دراسة العلاقة بين تغيرات متوسط درجة الحرارة اليومية وعدد الإصابات الجديدة اليومية بفيروس كورونا، خلال الفترة الممتدة من 01 أفريل 2020 إلى 30 نوفمبر 2020، باستخدام منهجية التكامل المشترك. وتبين من الدراسة عدم وجود علاقة ارتباط بين درجة الحرارة وانتشار فيروس كورونا الجديد في الجزائر، كما لا توجد علاقة سببية من درجة الحرارة نحو عدد حالات الإصابة بالفيروس. كما اتضح من خلال النمذجة القياسية وفق منهجية التكامل المشترك عدم وجود أي أثر لدرجة الحرارة على حالات الإصابة بفيروس كورونا في الجزائر سواءا على المدى القصير أو على المدى الطويل. وهذه النتائج المتوصل إليها تتوافق مع أراء العديد من الخبراء ونتائج الكثير من الدراسات. فحتى وإن كان لدرجة الحرارة تأثيرا على انتشار فيروس كورونا الجديد، فإن هذا التأثير يعتبر ضعيفا جدا إذا ما قورن بعوامل أخرى، خاصة منها المرتبطة بالالتزام بالإجراءات الوقائية وتدابير الحجر الصحي والتباعد الاجتماعي، وتنقل الأفراد داخليا وخارجيا، ومدى تطور القطاع الصحي، إلى غير ذلك من العوامل الهامة. The aim of this paper is to analyse and measure the effect of temperature on the spread of the Corona virus in Algeria. By studying the relationship between daily average temperature changes and the number of daily new infections with the Coronavirus, during the period from April 01, 2020 to November 30, 2020 using the co-integration methodology. The study revealed that there is no correlation between temperature and the spread of the new Corona virus in Algeria, and there is no causal relationship from temperature towards the number of virus cases. It was also evident through econometric modeling according to the cointegration methodology that there was no effect of temperature on cases of infection with the Coronavirus in Algeria, either in the short term or in the long term. These results are consistent with the opinions of many experts and with the results of many studies. Even if the temperature has an effect on the spread of the new Corona virus, this effect is considered very weak when compared to other factors, especially those related to adherence to preventive measures, quarantine measures, social distancing, the movement of individuals internally a,nd externally, and the extent of the development of the health sector to other important factors
مقال
Keywords: فيروس كورونا الجديد كوفيد-19 ; درجة الحرارة ; تكامل مشترك ; نموذج تصحيح الخطأ